2020
DOI: 10.1111/jne.12914
|View full text |Cite
|
Sign up to set email alerts
|

Huperzine‐A administration recovers rat ovary function after sympathetic stress

Abstract: Chronic cold stress affects ovarian morphology and impairs fertility in rats. It causes an ovarian polycystic ovary (PCOS)‐like phenotype, which resembles PCOS in women. The mechanism of cold stress action involves increased ovarian noradrenaline (NA) levels, which remain elevated after cessation of cold stress. By contrast, ovarian acetylcholine (ACh) levels are only transiently elevated and returned to control levels after a 28‐day post stress period. Because ACh can exert trophic actions in the ovary, we hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…This treatment elevated intraovarian ACh, increased numbers of healthy antral follicles, corpora lutea, and enhanced fertility success in female rats (Urra et al, 2016 ). These changes could conceivably be a direct consequence of higher intraovarian ACh levels and activation of cholinergic receptors in the ovary (Benitez et al, 2021 ; Riquelme et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This treatment elevated intraovarian ACh, increased numbers of healthy antral follicles, corpora lutea, and enhanced fertility success in female rats (Urra et al, 2016 ). These changes could conceivably be a direct consequence of higher intraovarian ACh levels and activation of cholinergic receptors in the ovary (Benitez et al, 2021 ; Riquelme et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that HupA increased intraovarian ACh levels and changed ovarian follicular development, as evidenced by increased numbers of healthy antral follicles, corpora lutea, and enhanced fertility success in the rat (Urra et al, 2016 ). It appears possible that these changes are direct consequences of higher ACh levels and activation of specific cholinergic receptors in the ovary (Benitez et al, 2021 ; Riquelme et al, 2020 ), thus the hypothesis to be tested is that ACh from local origin acts on ovarian follicles through muscarinic receptors present in ovarian cells of the follicle.…”
Section: Introductionmentioning
confidence: 99%
“…in which they demonstrated that the increase in ACh in a normal ovary induced an increase in ovulation and fertility. In addition this is a characteristic of ACh because it is able to reverse the PCO phenotype induced by cold stress in rats ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…If this is correct, we either can suggest that NGF acting on sympathetic nerves increases NE in the ovary by a direct effect of NGF or induced by stress ( 11 , 12 ) and can participates in the development of the PCO phenotype in rat. It probably acts increasing the ACh concentration whose participation in ovary physiology is just recently been considered ( 4 , 13 ); much less is know in pathological conditions such as the PCO phenotype in rat.…”
Section: Introductionmentioning
confidence: 99%
“…Riquelme [ 51 ] showed that when ACh esterase was blocked in rats exposed to cold stress (4 °C for 3 h day for 28 days), ovarian levels of both NA and ACh were elevated, and fewer cysts and normal testosterone and estradiol plasma levels were found. In the present study, it was observed that the blockage of the cholinergic system by the administration of atropine to animals previously treated with EV increased the number of healthy follicles and decreased follicular atresia, as well as the number of cysts.…”
Section: Discussionmentioning
confidence: 99%